IN TURKISH NATIONAL TEAM SKIERS AND JUDO ATHLETE’S PERFORMANCE - Koca, Feyzullah (Acta Scientiae et Intellectus, 2024)
The purpose of this study was examined variations in skiers and judo athlete’s performance, and to the variation in different aerobic and anaerobic variables. Fifty Turkish skiers and judo athletes were used, competing at the national and international levels. Independent simple-t tests were done statistical analysis. Age and Body weight was higher in judo athletes than skiers. Skiers were aerobic power 47.81 ml/kg/min, anaerobic power 97.72 kg-m/sec, Body fat % 10.73, Number Sit up 27.99 repetition. 50 m sprint time 7.70 sec, Shuttle Run 20.51 sec, and Sit and Reach Flexibility test 21.37 cm. Judo athletes were aerobic power 52.21 ml/kg/min, anaerobic power 132.27 kg-m/sec, Body fat % 9.06, number of Sit up 32.0 repetition, 50 m sprint time 7.25 sec, Shuttle Run 19.52 sec, and Sit and Reach Flexibility test 25.34 cm. There was significant difference in Body fat %, Aerobic power and anaerobic power, Sit up, 50 m sprint time, Shuttle Run, and Sit and Reach Flexibility of the judo and skier groups (p<0,05 and p<0,001). Judo athletes have better values than skiers. For high performance in male Turkish national ski and judo athletes are aerobic and anaerobic power, durability and speed capacities low. Coaches must use training programs to optimize physiological adaptations and increase performance in ski and judo.